Design and implementation of an air traffic visualisation system involving 2D and 3D displays with touch interaction - Foo, Gary Hee Wei (2016)
As air traffic globally is poised to grow in the coming decades, this will inevitably lead to an increase in the workload of the air traffic control officers (ATCOs). As a result, the ATCOs may suffer from a decrease in situational awareness due to mental stress. At best, this may hamper their performance but in some cases, a violation of safety regulations may surface. Therefore, this project proposes the display of air traffic situations to the ATCOs using a novel 3 dimensional projection in addition to the conventional 2 dimensional bird-eye view. This system will allow the ATCOs to maintain similar high standards of performance yet with less cognitive resources such that they are in a better state of mind to make decisions. This project also investigates the feasibility of using only touch controls to interact with the system and across the 2D and 3D displays. The visualisation system is written using web based technologies, with the 3D projections rendered by the X3DOM library. A generic touchscreen is then used to interact with the system in the tests. A brief user study conducted indicates that the design ideas and the features are novel and have great potential. Future work may include improving customisation towards users for them to adjust various system settings as well as using a more appropriate computing technology to power the visualisation system.